2017
DOI: 10.1097/md.0000000000008249
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with abdominoperineal resection (APR) and low anterior resection (LAR) who had very low rectal cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…were compared. 49 The overall recurrence rates were 37% and 27%, respectively, and RFS did not differ according to the mode of surgery for different cancer stages.…”
Section: Prognosis Links To the Surgery: Apr Versus Isrmentioning
confidence: 78%
“…were compared. 49 The overall recurrence rates were 37% and 27%, respectively, and RFS did not differ according to the mode of surgery for different cancer stages.…”
Section: Prognosis Links To the Surgery: Apr Versus Isrmentioning
confidence: 78%
“…Most studies (including the largest of its kind to date (21)), report that a LAR overall produces a higher survival rate than an APR (paradoxically the disease-free survival rates were suggested to be very similar). Though ndings were commonly confounded by the fact, that the tumours of the patients were relatively high from the anal verge, and that the subgroups had different PCRT rates (22,23). Most studies on the subject of local failure indicate greater rates with APR.…”
Section: Discussionmentioning
confidence: 99%
“…After exclusion of reports or reviews or meeting abstracts, 12 studies finally remained. [11][12][13][14][15][16][17][18][19][20][21][22] The study characteristics, number of patients, matching, and the scores of the quality assessment of each study are summarized in Table 1. There were 11 retrospective studies and 1 prospective observational study, but no RCTs.…”
Section: Studies Selection and Quality Assessmentmentioning
confidence: 99%
“…Regarding the survival of patients, we used the 5-year OS rate, 5-year DFS rate, and 3-year LAR to reflect. Eight studies 11,13,14,16,17,19,21,22 reporting on DFS showed no significant differences between ISR and APR (hazard ratio [HR] = 0.98; 95% CI = 0.79 to 1.20; P = .82; Figure 5), without significant heterogeneity (χ 2 = 5.18, df = 7, P = .64; I 2 = 0%) and publication bias (Egger's test: P = .05). Similarly, no significant differences were noted in 5-year OS rate (HR = 1.12; 95% CI = 0.70 to 2.14; P = .48) and 3-year LAR (HR = 1.20; 95% CI = 0.78 to 1.87; P = .41) between the 2 groups.…”
Section: Survival Of Patientsmentioning
confidence: 99%